STRATEGI AMERIKA SERIKAT DALAM MENGHADAPI ESKALASI CYBERPOWER CHINA TAHUN 2015-2019 - Ramadani Pasaribu; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The rapid development and advancement of technology in the 21st century brings the term cyberpower as a new concept in international relations. over the last few decades China has become very aggressive in its technological advancements and wants to become cyberpower immediately as Xi-Jinping's speech in 2013. The escalation of China's cyberpower has had its own effect on America. on the one hand China with its intention as a cyberpower country can shift the position of the United States as the "dominant actor" and on the other hand China's escalation of cyberpower harms the United States with the number of attacks aimed at it. Significant and rapid changes in China in the last decade deserve the attention of many countries, especially America. In an effort to respond to these conditions, America released a new defense strategy known as the Defense-forward strategy. The defense-forward strategy reflects the basic concept of offensive as well as defensive defence. This strategy allowed America to conduct operations beyond its geographic boundaries. The defense-forward strategy is implemented with the following steps; enhance cyberpower capabilities, build China-US cyber security cooperation, build global collective defense alliances and seek to build American influence in cyberspace through the participation of multilateral organizations, recommending cyberspace norms and governance in accordance with US national values.Keywords: Cyberpower, Cyberspace, Defense-forward Strategy, United States of America, China, Cyber security-dilemma.